2017
DOI: 10.5026/jgeography.126.533
|View full text |Cite
|
Sign up to set email alerts
|

The Resilience of Local Communities: The Great East Japan Earthquake and a Relocation Project in the Moune District of Kesennuma City, Miyagi Prefecture

Abstract: A tsunami caused by the Great East Japan Earthquake on March 11, 2011, devastated coastal areas of Sanriku in northeastern Japan. Because Sanriku had been damaged repeatedly by tsunamis in the past, local governments and residents attempted to protect coastal communities by building large tide embankments, raising the ground, and relocating houses to higher ground. Geographical studies on the disaster mainly focus on the vulnerability of regional communities to disasters and on measures taken to reduce hazard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
1
1
Order By: Relevance
“…The women were encouraged by their children and acquaintances, received support from their peers, and sometimes extended a helping hand to others. Previous research did not report any resilience associated with helping others; the fact that the affected women performed a supportive role is a new finding from the present study, although it has been reported that mutual help between residents during a disaster is essential for recovery (Yagazaki, 2017). Therefore, resilience may also be necessary during disasters.…”
Section: Characteristics Of Resilience Of Affected Pregnant and Postpartum Womencontrasting
confidence: 49%
“…The women were encouraged by their children and acquaintances, received support from their peers, and sometimes extended a helping hand to others. Previous research did not report any resilience associated with helping others; the fact that the affected women performed a supportive role is a new finding from the present study, although it has been reported that mutual help between residents during a disaster is essential for recovery (Yagazaki, 2017). Therefore, resilience may also be necessary during disasters.…”
Section: Characteristics Of Resilience Of Affected Pregnant and Postpartum Womencontrasting
confidence: 49%
“…This was generally observed in the way that the local communities dealt with nature and natural disasters. Thus, they have created so‐called “disaster resiliency.” Resiliency of this kind teaches local people how to become united to confront any obstacles (Yagasaki, ), not only in times of disaster but also in daily life. A student commented on this point as follows: “Because local people are always living in an unpredictable rhythm with nature, they are always ready to face any change and to act towards solutions.…”
Section: Discussionmentioning
confidence: 99%